Uma unidade de ensino potencialmente significativa como proposta para o ensino dos alimentos e seus nutrientes - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The pedagogical interventions that include sequences of teaching that work in a dynamic and organized way with the content stimulate the student's interest in knowledge. The present dissertation presents as a research problem: "How to evaluate if a pedagogical intervention, proposed through a potentially significant teaching unit, will contribute to the students' learning development in relation to the constitution and function of food?". This pedagogical intervention was implemented in a group of the eighth year of elementary school, during the science classes, in the Oswaldo Aranha State Educational Institute, located in the city of Alegrete – RS. The present research is characterized by having a qualitative, descriptive approach that occurred between June and August 2017. The pedagogical interventions that were performed are based on the theory of meaningful learning proposed by Ausubel. In carrying out some activities of the proposed didactic sequence, the students used an application developed in this project, with the purpose of working the content and assisting in the research. To collect the data were used instruments such as the materials produced by the students, the photos of the materials produced and the students doing the work, filming some presentations and the evaluation activities: initial and final. The pedagogical rubrics were used to evaluate the work produced in the groups.The data collected were studied and described. These were analyzed and compared to the theory used in project development. With the development of this research it was possible to verify that the potentially significant teaching unit contributed to the acquisition of knowledge about the nutrients and their actions in the body. And the use of a technological resource helped the students in the accomplishment of the works and in the understanding of the nutritional table of the foods
Keywords: Ensino de ciências; Tecnologia da informação e comunicação; Unidade de ensino potencialmente significativa; Science teaching; Information and communication technology; Potentially significant teaching unit; CNPQ::CIENCIAS SOCIAIS APLICADAS